Inovasi dalam Organisasi Pendidikan: Kepekaan, Proses, dan Pengambilan Keputusan: Penelitian - Muhammad Farhan Ferdino; Fajri Ismail; Muhammad Win Afgani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
In an educational organization, innovation plays a crucial role in enhancing the effectiveness and quality of learning. Therefore, educational institutions are required to possess sensitivity, a structured process, and precise decision-making to achieve these goals. The objective of this study is to understand the concept of innovation within educational organizations, along with their sensitivity, processes, and decision-making mechanisms. The research method employed is a literature review, with data collected from relevant articles, manuscripts, and books on educational innovation. A descriptive data analysis technique is used to analyze the gathered information. The findings of this study conclude that innovation in educational organizations is a critical element in improving the efficiency of the education system and supporting the achievement of educational goals. Through innovation, institutions become more adaptive and capable of producing competitive graduates. By comprehending each stage of the innovation process and the factors influencing decision making whether individual, collective, authoritative, or contingent educational organizations can become more adaptive and responsive to change, thereby creating a learning system that aligns with global demands.